A powerful dual-responsive soft actuator and photo-to-electric generator based on graphene micro-gasbags for bioinspired applications. Issue 31 (27th June 2018) - Yang, Lulu; Qi, Ke; Chang, Longfei; Xu, Aifeng; Hu, Ying; Zhai, Hua; Lu, Pin
Abstract : High-performance dual-responsive soft actuators with internal graphene micro-gasbags are fabricated and used to realize diverse biomimetic motions. Abstract : Soft actuators with large deformation and high output force in response to multi-stimuli are highly demanded for the development of biomimetic applications. Here, a bilayer actuator composed of spongy graphene with internal gasbag microstructures and the commercial polyimide adhesive tape is fabricated by a simple and fast method. This actuator produces large deformation, high output force, and dual-stimuli response, owing to the deformation of graphene micro-gasbags coupled with the thermal expansion of polyimide, and the electrothermal and photothermal properties of graphene. Experiments show that upon low voltage (16 V) stimulation the fabricated actuator with a length of 30 mm could generate a bending curvature of 0.55 cm −1 in 5 s, and can simultaneously produce high output force and lift an object 20 times heavier than its own weight. Moreover, a curvature of 0.45 cm −1 can be achieved for the actuator upon light irradiation for 10 s. Based on this bilayer actuator, diversely biomimetic motions including kicking a ball, grabbing a vegetable leaf, human hand movement, and creeping motion are realized, revealing its potential application in soft robotics, artificial muscles, wearable electronics, and biomedical devices. Besides the mechanical deformation output, a photo-to-electric generator is also assembled by associating this actuator with commonly triboelectric materials, further enriching the application range of soft actuators.